2021
DOI: 10.1094/pdis-01-21-0110-re
|View full text |Cite
|
Sign up to set email alerts
|

The Population of Sclerotinia sclerotiorum in Brazil Is Structured by Mycelial Compatibility Groups

Abstract: The genetic structure of the population of Sclerotinia sclerotiorum was analyzed using 238 individuals collected from different hosts. Individuals were characterized for microsatellite genotypes and mycelial compatibility groups (MCGs). A total of 22 MCGs and 64 multilocus lineages (MLLs) were identified. There was a close relationship between the MCGs and MLLs, but there was no association between MLLs and hosts or regions. At least 39 MCGs are present in Brazil and 68.5% of the isolates were assigned to eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…However, in a subsequent study using linkage disequilibrium measures, Lehner et al (2015) reported that despite the relatively high genotypic diversity observed among isolates, the SSR loci were in linkage disequilibrium, and thus, the S. sclerotiorum population had a clonal genetic structure. These results were later supported in larger studies, where the pathogen population of Brazil not only remained clonal but also structured according to MCGs (Lehner et al, 2019;Silva et al, 2021). Silva et al (2021) analyzed 238 isolates, and only 22 MCGs and 64 SSR haplotypes were found, with no association between SSR haplotypes and MCGs.…”
Section: White Moldmentioning
confidence: 72%
See 4 more Smart Citations
“…However, in a subsequent study using linkage disequilibrium measures, Lehner et al (2015) reported that despite the relatively high genotypic diversity observed among isolates, the SSR loci were in linkage disequilibrium, and thus, the S. sclerotiorum population had a clonal genetic structure. These results were later supported in larger studies, where the pathogen population of Brazil not only remained clonal but also structured according to MCGs (Lehner et al, 2019;Silva et al, 2021). Silva et al (2021) analyzed 238 isolates, and only 22 MCGs and 64 SSR haplotypes were found, with no association between SSR haplotypes and MCGs.…”
Section: White Moldmentioning
confidence: 72%
“…These results were later supported in larger studies, where the pathogen population of Brazil not only remained clonal but also structured according to MCGs (Lehner et al, 2019;Silva et al, 2021). Silva et al (2021) analyzed 238 isolates, and only 22 MCGs and 64 SSR haplotypes were found, with no association between SSR haplotypes and MCGs. Although their clonal lineages were widely distributed in space and persistent over time, evidence of some degree of outcrossing was detected (Silva et al, 2021).…”
Section: White Moldmentioning
confidence: 72%
See 3 more Smart Citations